Analisis Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Nilai Akhlak terhadap Budaya Kerja Bank Syariah Indonesia di Jember - Ahmad Akbar Maulana Syarif Hidayatullah; Ana Pratiwi (MASALIQ, 2026)
Although Bank Syariah Indonesia (BSI) plays a strategic role in expanding Islamic financial inclusion in Indonesia, studies that specifically examine the effect of leadership differences on work motivation and work culture grounded in AKHLAK values within the Islamic banking environment remain limited. This study aims to analyze the influence of leadership style, work motivation, and AKHLAK values on the work culture of Bank Syariah Indonesia in Jember, both partially and simultaneously. This study employed a quantitative method with a survey approach and an associative research type. The research population included employees at five BSI branch offices in Jember, namely KC Jember Sudirman, KCP Jember Gajah Mada, KCP Jember Balung, KCP Jember Kencong, and KCP Jember Tanggul, with a sample of 100 respondents selected through a non-probability sampling technique using a purposive sampling approach. Data were collected using a questionnaire and analyzed through validity testing, reliability testing, descriptive analysis, classical assumption testing, multiple linear regression, the t-test, and the f-test. The results showed that leadership style, work motivation, and AKHLAK values each had a significant partial effect on work culture. In addition, these three variables also had a significant simultaneous effect on work culture. These findings emphasize the importance of leadership style, work motivation, and the internalization of AKHLAK values in shaping work culture in Islamic banking. This study contributes to enriching the study of sharia-based human resource management and provides practical implications for formulating human resource development strategies, strengthening work motivation, and internalizing AKHLAK values more effectively within Bank Syariah Indonesia.